Pengembangan E-Modul berbasis Website untuk Pengoptimalan Pembelajaran Daring pada Mata Kuliah Anatomi Tumbuhan - Taufik, Ainul Uyuni; Hasanah, Ummul; Alamsyah (Faculty of Tarbiyah and Teacher Training, 2024)
This research aims to develop website-based e-module learning media to optimize online learning in plant anatomy courses in the Biology Education Study Program at UIN Alauddin Makassar. This research and development research uses the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. Data collection instruments include validation sheets, questionnaires, and learning outcomes tests. The data analysis technique is related to measuring the validity, practicality and effectiveness of website-based e-modules. The research results show that the website-based e-module learning media for optimizing online learning in plant anatomy courses meets the valid, practical and effective categories. Based on the results of validity and practicality, this media is suitable and practical for use as a learning medium in plant anatomy courses, especially in blended learning.